2020
DOI: 10.1101/2020.08.20.259242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Modeling of Virus Particle Propagation and Infectivity along the Respiratory Tract: A Case Study for SARS-COV-2

Abstract: Respiratory viruses including Respiratory syncytial virus (RSV), influenza virus and cornaviruses such as Middle Eastern respiratory virus (MERS) and SARS-CoV-2 infect and cause serious and sometimes fatal disease in thousands of people annually. It is critical to understand virus propagation dynamics within the respiratory system because new insights will increase our understanding of virus pathogenesis and enable infection patterns to be more predictable in vivo, which will enhance targeting of vaccines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This demonstrated the conjecture that the nasopharynx served as the seeding region for the contamination of the lower airway via aspiration of SARS-CoV-2-laden boluses of nasopharyngeal fluids (Basu and Chakravarty, 2020). It is noted that a few previous studies associating virus infection with in silico models have been reported and summarized (Daun and Clermont, 2007;Vaziri and Gopinath, 2008;Ciupe and Heffernan, 2017;Vimalajeewa et al, 2020). It is not hard to see that there is still a long way to go to unravel the mysteries of biomechanics in virus infection by in silico models.…”
Section: Organ-on-a-chipmentioning
confidence: 89%
“…This demonstrated the conjecture that the nasopharynx served as the seeding region for the contamination of the lower airway via aspiration of SARS-CoV-2-laden boluses of nasopharyngeal fluids (Basu and Chakravarty, 2020). It is noted that a few previous studies associating virus infection with in silico models have been reported and summarized (Daun and Clermont, 2007;Vaziri and Gopinath, 2008;Ciupe and Heffernan, 2017;Vimalajeewa et al, 2020). It is not hard to see that there is still a long way to go to unravel the mysteries of biomechanics in virus infection by in silico models.…”
Section: Organ-on-a-chipmentioning
confidence: 89%
“…Many approaches do consider k c in the steadystate, but we like to draw attention by the community that it can have non-linear relationships with the infected humans, so it should also be associated with different disease stages over time that is bounded by transition probabilities of stage changes (severe stage to mild, and vice versa). Moreover, as shown in both (20) and (21), that non-linearities do exist, for example, the relationship V r (t) P v (t) is added to the model but is currently non-existing in the literature. The initial virus concentration V 0 can be directly obtained from values in Table I.…”
Section: B Extra-body Molecular Communications Modelsmentioning
confidence: 99%
“…There are three main blocks in the model: the droplets entrance rate, the mouth-lung propagation, and the virus replication and deposition rates. The general model of virus propagation is based on a governing equation based on the Fick's second law for advection-diffusion investigated in [20]. This model accounts for the concentration of the virus in a particular branch of the respiratory tract G i , and can be represented as…”
Section: B Extra-body Molecular Communications Modelsmentioning
confidence: 99%
See 2 more Smart Citations